(untitled) (Transport systems and technologies, 2018)
The article considers the role of information systems for participants in the supply chain. The reasons that prompt organizations to implement complex information systems are, on the one hand, the desire to increase the productivity of their work, and on the other hand the desire to improve the efficiency of enterprise management by adopting optimal and rational management decisions. The accumulated information due to the operation of the information system for many organizations is an important asset, however, it is becoming more and more difficult to process it and to benefit from it every day. It is established that it is impossible to simply talk about the necessary, important and correct information that an enterprise can use in its work. Now it becomes necessary to talk about the speedy reception, processing, storage, transfer of unstructured, heterogeneous data, which gives the opportunity to obtain qualitatively new knowledge for the enterprise due to a comprehensive analysis of all information in a single analytical storage (combined storage facilities). It is determined that the development and implementation of information interaction between corporate information systems of participants in the entire transport process from the manufacturer to retailers will provide a number of advantages, including: the adoption of effective management decisions, the ability to automate the processing of a large amount of information, the ability to plan their work and resources for all participants Transport process.